Atomic layer deposition of Pd and Pt nanoparticles for catalysis: on the mechanisms of nanoparticle formation. (4th December 2015) - Mackus, Adriaan J M; Weber, Matthieu J; Thissen, Nick F W; Garcia-Alonso, Diana; Vervuurt, René H J; Assali, Simone; Bol, Ageeth A; Verheijen, Marcel A; Kessels, Wilhelmus M M
Abstract: The deposition of Pd and Pt nanoparticles by atomic layer deposition (ALD) has been studied extensively in recent years for the synthesis of nanoparticles for catalysis. For these applications, it is essential to synthesize nanoparticles with well-defined sizes and a high density on large-surface-area supports. Although the potential of ALD for synthesizing active nanocatalysts for various chemical reactions has been demonstrated, insight into how to control the nanoparticle properties (i.e. size, composition) by choosing suitable processing conditions is lacking. Furthermore, there is little understanding of the reaction mechanisms during the nucleation stage of metal ALD. In this work, nanoparticles synthesized with four different ALD processes (two for Pd and two for Pt) were extensively studied by transmission electron spectroscopy. Using these datasets as a starting point, the growth characteristics and reaction mechanisms of Pd and Pt ALD relevant for the synthesis of nanoparticles are discussed. The results reveal that ALD allows for the preparation of particles with control of the particle size, although it is also shown that the particle size distribution is strongly dependent on the processing conditions. Moreover, this paper discusses the opportunities and limitations of the use of ALD in the synthesis of nanocatalysts.